Knowledge, attitudes, and current practices toward lung cancer palliative care management in China: a national survey - Chen, Mengting; Hui, Suocheng; Huang, Yalan; Yu, Huiqing; Yang, Hong; Yang, Liejun; Tian, Ling; Wang, Sixiong (Frontiers in Oncology, 2024)
The present investigation seeks to illuminate the current state and disparities in the knowledge, attitudes, and practices (KAP) among healthcare professionals regarding the management of lung cancer palliative care (LCPC) in China, while simultaneously assessing the prevalence and context of patient-controlled analgesia (PCA) usage in the management of cancer-related pain.Methods: A total of 2093 healthcare practitioners from 706 hospitals across China completed a structured questionnaire that probed various facets of LCPC management.The questionnaire consisted of seven thematic sections, incorporating chi-square tests and Fisher's exact probabilities to statistically assess the discrepancies in KAP among healthcare professionals across different hospital grades. Ordered data distributions among hospital grades were compared using non-parametric Kruskal-Wallis H and Mann-Whitney U tests. Multiple-choice items were subjected to multiple-response cross-tabulation analysis, while the Spearman rank-order correlation coefficient was employed to gauge potential associations among variables.Results: Around 84.2% of the respondents perceived anti-tumor therapy to be of equal importance to palliative care. Statistically significant differences (χ² = 27.402, P = 0.002) in satisfaction levels were observed, with participants from Tertiary hospitals demonstrating higher satisfaction compared to those from Secondary and Primary hospitals. Pain emerged as the most prevalent symptom necessitating LCPC. Major impediments to LCPC adoption included patients' and families' concerns about the safety of long-term palliative care-related drug use. 31.1% of the respondents cited the most frequent rationale for PCA use as cases involving patients who required systemic administration of large opioid doses or exhibited intolerable adverse reactions to opioids. The principal deterrents against the use of PCA for cancer pain management were: (1) apprehension about adverse drug reactions due to overdose, (2) concern about the potential for opioid addiction, and (3) the anticipated increase in patients' economic burdens. Over the preceding 24-month period, 33.9% of the surveyed healthcare practitioners reported no engagement in either online or offline LCPC-related training initiatives.This study emphasizes the pressing need for comprehensive training in LCPC among Chinese health personnels, particularly focusing on the effective management of cancer pain symptoms.